Application of Circuit Model for Photovoltaic Energy Conversion System - Natarajan Pandiarajan; Ramabadran Ramaprabha; Ranganath Muthu (International Journal of Photoenergy)
Circuit model of photovoltaic (PV) module is presented in this paper that can be used as a common platform by material scientists and power electronic circuit designers to develop better PV power plant. Detailed modeling procedure for the circuit model with numerical dimensions is presented using power system blockset of MATLAB/Simulink. The developed model is integrated with DC-DC boost converter with closed-loop control of maximum power point tracking (MPPT) algorithm. Simulation results are validated with the experimental setup.